Organizational Strategy Execution: From Planning To Reality A Literature Review On Key Success Factors For Strategy Implementation In A Dynamic Environment, The Case Of Indonesian Organizations - Rudiyanto Rudiyanto; Arief Prayitno (Asian Journal of Social and Humanities, 2025)
Many organizations fail to achieve their strategic goals not due to poor planning, but because of weak strategy execution. Strategy execution is a critical stage that requires the involvement of top management, adaptive control systems, and support from mature performance measurement and risk management systems. This research aims to analyze the factors that influence the success and failure of strategy execution in dynamic environments, with a specific focus on Indonesian organizations. The research method employed is qualitative, with a systematic literature review approach, utilizing various relevant academic sources from international and local databases. The findings indicate that successful strategy execution is characterized by leadership commitment, risk prioritization, stakeholder involvement, periodic evaluations, and the integration of risk management throughout the strategic process. Conversely, failure in strategy execution is often caused by a lack of risk awareness, an unsupportive organizational culture, and the absence of a structured performance measurement system. In conclusion, effective strategy execution emerges from the deliberate alignment of three foundational pillars: structural organizational readiness, strong and accountable leadership, and an integrated system of performance and risk oversight. Organizations that cultivate balance across leadership commitment, adaptive control systems, and risk-performance integration are better positioned to transform strategic plans into tangible and sustainable outcomes, even amid dynamic environmental challenges. By managing these elements effectively, organizations can bridge the persistent gap between strategic intent and operational reality.